Recent Publications (Quarterly Journal of Economics, 1940)
Recent Publications Get access The Quarterly Journal of Economics, Volume 55, Issue 1, November 1940, Pages 170–173, https://doi.org/10.1093/qje/55.1.170 Published: 01 November 1940